PENGARUH MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR PADA MATERI KOLOID - Lidiya, Lidiya; Enawaty, Eny; Hadi, Lukman (Universitas Tanjungpura, 2025)
Bassed on the results of interviews with one student of class XI IPA at SMA Permata Kasih that the practicum is very rarely done and the learning model used is lecture, making students feel bored and chemistry is very difficult tu understand. To make students more active in the practicum process, a project-base learning model was used in this study. The purpose of this study was to determine the effect of project-based learning models on learning outcomes.The research method used by students with an unequal control group design research desing. The sample in this study is class XI IPA 1 and IPA 2.The data analysis used is the U-Mann Whitney test with the posttest value of the control class and the experimental class, namely asmpy Sig.(2-Tailed is 0.02, meaning that there is a difference in learning outcomes between students taught using a project- based learning model and students taught using the lecture method. Based on the result of the calculation of the effect size obtained a score of 1.28 and is classified in the high category. Meaning that is has an effect of 39.975% on student lerning outcomes